2021
DOI: 10.1002/adpr.202000019
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved Nonlinear Diffuse Femtosecond‐Pulse Reflectometry Using Lithium Niobate Nanoparticles with Two Pulses of Different Colors

Abstract: Time‐resolved nonlinear optical sum‐frequency generation (SFG) of two differently colored, infrared (sub‐)picosecond laser pulses is studied by means of nonlinear diffuse femtosecond‐pulse reflectometry using lithium niobate nanoparticle pellets. The visible SFG emission exhibits an asymmetric pulse shape in the time domain which is explained within the framework of light propagation in random media. The analysis of the spectro‐temporal data set indicates that LiNbO3 nanoparticle pellets can be used for an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In stark contrast to the conventional optical pulse duration measurement method such as standard autocorrelation and GRENOUILLE, the proposed strategy provides notable advantages, including high accuracy and easy operation (see Table S5, Supporting Information for details). [38][39][40] In addition, the approach also enables to remove the alignment constraints imposed by the complicated mechanical devices.…”
mentioning
confidence: 99%
“…In stark contrast to the conventional optical pulse duration measurement method such as standard autocorrelation and GRENOUILLE, the proposed strategy provides notable advantages, including high accuracy and easy operation (see Table S5, Supporting Information for details). [38][39][40] In addition, the approach also enables to remove the alignment constraints imposed by the complicated mechanical devices.…”
mentioning
confidence: 99%
“…In these cases, two light pulses of different photon energies ω 1 , ω 2 are mixed in the nanoparticle and generate either the sum (ω 1 + ω 2 ) or the difference frequency (ω 1 − ω 2 ) at the output. The sum and difference frequency conversion in HNPs has already been demonstrated in previous studies [44,45] and appears concurrently to harmonic generation, as shown in [45], thus extending the concept of multi-harmonic imaging, which was previously limited to the simultaneous acquisition of SHG and THG [17,25]. SFG and DFG give even more freedom in the tailoring of the excitation and emission according to the biological windows.…”
Section: Perspective Of Our Findings For Nir-microscopymentioning
confidence: 63%
“…It was shown that the method is sensitive to particles in the upper layers of the surface, as the penetration depth of the pulse into the powder sample is limited to a few tens of microns. At the same time, it is independent of the light polarization, as the incident polarization state is lost after multiple scattering events [21,26]. In our case, the method is used to demonstrate gap-free emission of SHG and THG, as well as to validate the harmonic nature of the generated signals in LNT nanocrystallites.…”
Section: Nonlinear Diffuse Femtosecond Pulse Reflectometrymentioning
confidence: 95%